Aortic Compression and Cross Clamping in a Case of Placenta Percreta and Amniotic Fluid Embolism: A Case Report - Belfort, Michael A.; Zimmerman, John; Schemmer, Glenn; Oldroyd, Ronald; Smilanich, Robert; Pearce, Michael (American Journal of Perinatology Reports, 2011)
Amniotic fluid embolism (AFE, also known as anaphylactoid syndrome of pregnancy) at the time of surgery for placenta percreta has been previously reported. We report here a case in which AFE and associated cardiac arrest occurred following a hysterectomy for placenta percreta. In this case, subhepatic manual aortic compression during the cardiac arrest and chest compressions followed by infrarenal aortic cross-clamping during volume infusion and reversal of the coagulopathy were associated with a successful resuscitation and good maternal outcome.
Keywords: Amniotic fluid embolism; placenta percreta; aortic cross clamping; bispectral index monitoring; zinc protoporphyrin